Odpowiedzi

2010-03-06T14:23:59+01:00
X+[x-z(z-x)]=x+[x-z²+zx]=x+x-z²+zx=2x-z²+zx

-(-a)+(-b+a)=a-b+a=2a-b

a-[b-(a+b)]=a-[b-a-b]=a-[-a]=2a

x-{x-[x-(x+1)-(x-1)-x]+(1-x)} =x-{x-[x-x-1-x+1-x]+(1-x)}=x-{x-[-2x]+1-x}=x-{2x+1}=x+2x-1=3x-1
2010-03-06T14:25:33+01:00
1) x+[x-z(z-x)] =
= x+[x-z²+zx] =
= x+x-z²+zx =
= 2x-z²+zx

2) -(-a)+(-b+a) =
= a-b+a = 2a-b

3) a-[b-(a+b)] =
= a-[b-a-b] =
= a-b+a+b = 2a

4) x-{x-[x-(x+1)-(x-1)-x]+(1-x)} =
= x-{x-[x-x-1-x+1-x]+1-x} =
= x-{x-x+x+1+x-1+x+1-x] =
= x-x+x-x-1-x+1-x-1+x =
= -x-1